Intention to visit Rainforest Discovery Centre (RDC) among student / Rosshera Roslan - Roslan, Rosshera (2019)
Nature tourism is important in development of country, due to the nature tourism can help the economic growth in the country and can attract more visitor to visit this country due to the Malaysia country has rich more interesting destination in nature tourism, this because Malaysia is the country of the area fully of forest due to the most of the area in Malaysia has the large hectar area of rainforest especially in Sabah still protected the area of virgin jungle class one. Meanwhile, Malaysia also has rich in flora and fauna this is the main attraction for tourist around the world to have the intention to visit in Malaysia especially in Sabah, has more beautiful nature and rainforest for them to explore. Nowadays nature tourism sector is becoming predomient important. Malaysia tourist arrival has large number of visitor from around the world to visit and explore our nature. The purpose of conducting this study is to identify the relationship of destination image, electronic word of mouth and perceived service quality can influence the intention to visit Rainforest Discovery Centre among student. In this research, the respondent were 175 questionnaire collected. Besides that, the data result based on the multiple regression analysis, shows destination image and perceived service quality is significant to influence the intention to visit Rainforest Discovery Centre among student. Based on the analysis, marketers need to improve and focusing about destination image due to the destination image and perceived service quality is more significant, that can influence the intention to visit of Rainforest Discovery Centre among student and other destination. Other than that, government should increase policies due to the visitor will have the intention to visit, when the place is safe and high security and improve infrastructure in nature tourism destination because most of the visitor will have the intention to visit the destination, when the destination have good infrastructure.